Urgensi Penerapan Pajak Karbon Di Indonesia - Selvi Selvi; Notika Rahmi; Idar Rachmatulloh (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to analyze the urgency of implementing a carbon tax in Indonesia. The research is a literature review using secondary data obtained from several sites on the internet and international journals. The results of the study suggest that carbon taxes are very necessary to be implemented in Indonesia given the deteriorating environmental conditions that affect the quality of public health, international emission reduction targets and as one of the strong reasons for not relying on fossil fuels.